Халықаралық көші-қонның тарихи сипаттамасы жəне көші-қон құқығы нормаларының қалыптасу барысы - Божқараұлы, А. (ҚарМУ басп., 2009)
Проблема миграции характеризуется особой сложностью, так как в ней переплетены не только правовые вопросы, но и вопросы социологии, демографии, политической экономии, эт- ногеографии, проблемы трудовых ресурсов в экономике. Среди них юридический аспект зани- мает особое место, поскольку от надлежащего правового обеспечения, регулирования и орга- низации процессов миграции зависит решение других вопросов, имеющих существенное значе- ние для жизнедеятельности общества. The problem of migration is characterizing with special complexity, as it covers not only legal aspects, but also the problems of sociology, demograthy, political economy, ethnogeography, the problems of labor resources in the economics. The legal aspect have the special important place, because the migration is closely connected with the legal security, regulation and organization of migration processes, from which depends other problems of essential value for living conditions of the society.